Traceability of Halal Control Point in Material, Production, and Serving to Support Halal Certification in Universitas Brawijaya Canteen - Sucipto, Sucipto; Hidayati, Luki; Perdani, Claudia Gadizza; Hasanah, Nur (UIN Sunan Gunung Djati Bandung, 2021)
Halal food certification in the university canteen needs to prepare Halal Assurance System (HAS) implementation. Halal Control Point (HCP) traceability in the canteen is very complicated because it has several menus, processes, and materials. This study aims to trace the HCP on materials, processing and serving in Universitas Brawijaya (UB) Canteen, then provide improvement. This research used seven criteria of HAS-23102 for a restaurant to evaluate the menus, ingredients, production, and serving in UB Canteen. HCP traceability was done on 60 menus from 4 food tenants and one beverage tenant. The results showed that grouping the menus and ingredients facilitates HCP identification. The menu consists of six groups: soup, deep-fried, stir-fried, strong spices dish, medium soup, and beverages. The materials consist of fresh ingredients, dry ingredients, and liquids. The menus required 113 materials. There are 16 (14%) materials HCP, including chicken, beef, noodles, and soy sauce. HCP materials do not meet HAS criteria and be replaced with halal-certified material or halal production process (HPP) description from the producer that needs to be checked by a halal auditor. The HCP did not found in the process and serving because the canteen does not produce and service haram (unlawful) products. Still, there is contamination possibility of haram and najis (unclean in Islamic terms) materials. For prevention, the Standard Operational Procedure (SOP) of production, serving the tenant, employee, and visitor need to be applied. The alternatives are supplying chicken meat and beef from a halal-certified slaughterhouse, monitoring and controlling the tenants' kitchen periodically three months, applying the halal standard for storage in tenant's kitchen and canteen facilities, and food serving in canteen. The HCP traceability of the university canteen according to halal standards, including raw materials, additional materials, processes, and serving, including the equipment used.